Adiponectin deficiency has no effect in murine autoimmune myocarditis. (April 2019) - Stroikova, Vera; Fischer, Andrea; Bockstahler, Mariella; Müller, Anna-Maria; Katus, Hugo A.; Kaya, Ziya
Abstract: Background: Adiponectin is a hormone that together with its receptors modulates a number of metabolic processes including gluconeogenesis and lipid catabolism. It belongs to the C1QTNF (complement C1q tumor necrosis factor-related protein) family, which has a variety of members with high amino acid sequence homology and overlapping functions. Concentration of adiponectin in blood is inversely correlated with body fat percentage and cardiac risk factors like blood pressure and CRP (C-reactive protein) level. Studies have identified the existence of a cardiac adiponectin system. However, little is known about the role of this system in the pathogenesis of autoimmune myocarditis. Thus, we have studied the involvement of adiponectin in the development of this autoimmune disorder in a mouse model of experimental autoimmune myocarditis (EAM). Methods: Adiponectin knockout (ko) and wild type (wt) mice were immunized with cardiac troponin I (cTnI) to induce an EAM. To determine the severity of myocardial damage, inflammation and fibrosis were scored after HE and Afog staining and high sensitivity troponin T (hsTnT) level was measured. To detect if changes in specific inflammatory cell numbers could be observed between the genotypes, we performed immunohistochemical staining to detect T lymphocytes, B lymphocytes and macrophages. The level of the humoral immune response was determined through the measurement of cTnI-specific serum IgG autoantibodies. Relative mRNA expression of different cytokines, C1QTNF family members and adiponectin receptors in the heart tissue was analyzed with qPCR. Results: Animals immunized with cTnI developed autoimmune myocarditis with a significant deterioration of cardiac parameters compared to the corresponding control group. The adiponectin ko group immunized with cTnI showed a tendency towards increased inflammation, fibrosis, heart-to-body-weight ratio, infiltration pattern of T lymphocytes, B lymphocytes and macrophages, hsTnT concentration, humoral immune response and mRNA expression of interleukin 6 in the heart tissue and decreased weight gain compared to the wt group immunized with cTnI. However, the difference to the wt group treated with cTnI was not significant. The analysis of cardiac mRNA expression of adiponectin receptors and four C1QTNF family members, most suitable for fulfilling the functions of adiponectin in adiponectin ko mice, did not show any significant differences between adiponectin ko and wt group at all. Conclusion: Our study reveals that the absence of adiponectin did not lead to a significantly increased impairment of cardiac function and was also unlikely to be compensated by its receptors or other C1QTNF family members in the murine model of EAM. Here, other synergistic or redundant effects might play a role and must be investigated in further studies to understand the role and function of adiponectin in autoimmune myocarditis.